Pembatalan Perkawinan Menurut Hukum Islam dan Akibat Hukumnya Terhadap Status Anak (KUA Kecamatan Medan Tembung) - Donita Simanungkalit; Riska Marpaung; Wulan Ayu Trisna; Syuratti A Rahayu Manalu (Pusat Riset dan Inovasi Nasional, 2023)
Annulment of a marriage is an action that states that the marriage bond that has been entered into is invalid according to the court's decision. The result is that the marriage is considered to have never existed. A marriage can be annulled if it does not meet the legal requirements. The research method used is qualitative descriptive with an empirical normative approach. The purpose of this paper is to understand the factors that cause marriage annulment and the legal consequences of marriage annulment on the status of children. The results of this research are that the effect of marriage annulment on the status of the child resulting from the marriage is called